Pengaruh Pengetahuan Pengelolaan Keuangan, Sikap Pengelolaan Keuangan, Dan Kepribadian Terhadap Perilaku Pengelolaan Keuangan UMKM Di Kota Padang - Humairah Khairunnisa; Riani Sukma Wijaya (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to determine the influence of financial management knowledge, financial management attitudes, and personality towards financial management behavior in UMKM (micro, small, and medium enterprises). The location of the object of this research is UMKM in Padang City. Data processed a result of disturbing questionnaires to 100 UMKM respondents. The results of this research show that data using statistical calculations via the SPSS version 23 application showed that (1) financial management knowledge had a significant positive effect on financial management behavior (2) attitudes financial management does not have a significant positive effect on financial management behavior (3) personality does not have a significant positive effect on financial management behavior